Moving Targets?: Exploring the Impact of Canadian Immigration and Security Legislation and Policies on Ottawa’s Muslim Communities - Laser, Christopher (Université d'Ottawa | University of Ottawa, 2014)
The purpose of this study is to begin exploring the effects of security and immigration laws and policies that may have had an effect on Muslims in Canada since 9/11, specifically in Canada’s capital city. Interviews were conducted in the summer and fall of 2014 to gather data on possible effects. The interview participants represented a range of roles within the Muslim community in Ottawa, including Imams, journalists, lawyers and non-profit workers. Each participant spoke to their understanding of the recent policies and laws and their impressions of effects that they might have on the community that they served or represented. The goal of this research is to conduct an exploratory study and begin to gather impressions of the effects of these policies in hopes that they can guide research that is ultimately aimed at reducing any experience of marginalization and discrimination felt by Muslims in Canada in relation to government security and immigration policies. The paper is divided into two main sections: Part A reviews key pieces of policy and legislation (pages 8-25), and Part B discusses some of the findings from the interviews (pages 25-36).